Online Training and Contests for Informatics Contestants of Secondary School Age - NÉMETH, N; ZSAKÓ, László (Journal of Education, Technology and Computer Science, 2015)
If you prepare students for programming contests carefully selected and widely available online training and contests offer help and diversity. If you teach about testing programs you have to know which sites offer downloadable tests or feedback with detailed test cases. If you want to make series of tasks for practicing you have to know which sites offer you categorized tasks of the appropriate level. In order to be able to choose from the available materials we need to categorize them. The previously defined and used criteria need some supplement criteria for better and sophisticated use of categorization from the teacher’s point of view. Online resources can be classified in general: what programming languages can be used, how often the contests are organized, in which languages they can be accessed, what types of problems a website deals with and at what level, what prior knowledge is required. We can group sites according to whether they help teachers to set tasks for their students, or get ideas for solutions or see the results of their students. Online contests can also be categorized regarding whether students can see each other’s solutions. The aim of this paper is to supplement the categorization and describe some major portals according to the previously defined and supplemented criteria.